2020
DOI: 10.4269/ajtmh.19-0311
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Health Perceptions and Beliefs Related to Zika Virus Exposure during the 2016 Outbreak in Northern Brazil

Abstract: During the 2016 Zika pandemic in Brazil, women's perceptions of infection risk, ability to adhere to Zika prevention strategies, or access to services following exposure were not emphasized in the public health response. Women in Fortaleza, Brazil, responded to a questionnaire on social factors related to perceived Zika risk and access to health care in June 2016. Data were coded using prespecified categories, and response frequency was reported. Of 37 respondents, most reported a lack of public services to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…A few studies mentioned that the use of a complicated, medical language or unkind behaviour in health facilities resulted in misconceptions and fear of questioning, especially in groups of people with lower education levels. [23, 30, 35, 48, 51, 54, 62, 73] Apart from clinic services or health professionals and providers, most popular sources of information and delivering messages were television, radio, word of mouth by family and friends, and social media [22, 32, 37, 38, 51, 53, 54, 56-58, 60, 62] Regarding the risks of a Zika virus infection, some studies reported scepticism towards the government and the media coverage about prevention measures because often, none of the immediate circle of acquaintances suffered from a confirmed Zika virus infection. Risk communication was perceived as way of spreading fear among populations by the government to raise sales and earnings of mosquito repellents or as invention to have an impact on fertility behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A few studies mentioned that the use of a complicated, medical language or unkind behaviour in health facilities resulted in misconceptions and fear of questioning, especially in groups of people with lower education levels. [23, 30, 35, 48, 51, 54, 62, 73] Apart from clinic services or health professionals and providers, most popular sources of information and delivering messages were television, radio, word of mouth by family and friends, and social media [22, 32, 37, 38, 51, 53, 54, 56-58, 60, 62] Regarding the risks of a Zika virus infection, some studies reported scepticism towards the government and the media coverage about prevention measures because often, none of the immediate circle of acquaintances suffered from a confirmed Zika virus infection. Risk communication was perceived as way of spreading fear among populations by the government to raise sales and earnings of mosquito repellents or as invention to have an impact on fertility behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Care-seeking women were given advice about mosquito prevention measures but did not receive information about the possibility of sexual transmission of Zika virus during pregnancy. [8, 22, 28, 38, 53, 56, 63, 70] This might be due to social taboos and religious reasons as Latin American countries are mostly catholic, and shame feelings around sexuality and difficulty in talking about sexually transmitted diseases for both, healthcare providers and community residents exist. Therefore, adequate communication of Zika virus risks should take place in healthcare services during antenatal check-ups and involve the male partners into comprehensive explanatory dialogues to get rid of false perceptions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Information on this mode of transmission was conveyed effectively by public health agencies and departments, which emphasized vector control as a prevention strategy. 11,12 However, the evidence of sexual transmission grew during the first few months of the outbreak in Brazil. 13 The risk of sexual transmission is higher among women who are pregnant or intend to become pregnant than among women who do not wish to become pregnant, because the former are less motivated to use condoms.…”
mentioning
confidence: 99%